An Analysis of Ontario Aboriginal Education Policy: Critical and interpretive perspectives - Cherubini, Lorenzo (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2010)
This paper provides an historical and contemporary interpretation of the developmental influences that have led to the Ontario Ministry of Education’s recent focus on Aboriginal educational policy in Ontario, Canada. It offers an interpretive and critical perspective on the rhetorical constructions, assumptions, and value-orientations implicit in two seminal documents. This discussion will assist Aboriginal Advisory Groups and communities, as well as policy-makers and practitioners, to think clearly about implementation strategies in the broader context of Aboriginal socio-educational development.